HUBUNGAN ASAL JURUSAN, STATUS EKONOMI ORANGTUA, DUKUNGAN SOSIAL KELUARGA DENGAN MOTIVASI BELAJAR PADA MAHASISWA SEMESTER IV - U Umdatus (Universitas Nahdlatul Ulama Surabaya, 2013)
Background: SomeHealth Science High Schoolshave students fromnon-science majors. Hypothesized,studentswould bemore motivatedtolearnif theyhave astrong foundationandrelevanceof sciencerelevant to themajorswhilein a high school. This studyaimed toanalyze the relationship of major origin withthe learning motivation by controlling the influence of parents’ economic statusandfamily social support. Subjects and Methods: This studywasan observationalanalyticstudywithcross sectional approach. The sample of45college students was selectedbystratified randomsamplingofthe student populationat S1 Nursing ScienceDepartment of Health SciencesIslamicFoundation HospitalSurabaya. Data collection was conductedfromMarch 10tillMarch 17, 2013. Independent variables studied includedmajororigin, economic status of parents, familysocialsupport, while thedependent variableis a learning motivation. Learning motivationandfamilysocialsupportwere measuredwith a questionnairethathadbeen tested. Datawere analyzed bymultiple logisticregression analysis model. Result & Conclusion: The result of the study concludes that there are relationshipmajororigin(OR =1.90, p=0.335), parentalsocioeconomic status(OR =0.72, p=0611) andfamilysocial support(OR = 1.47, p=0.536) with learning motivation although they are not statistically significant. The writer suggests that it still needs further studywitha larger samplesize.